Examining the Latent Structure of the BASC-3 BESS Parent Preschool Form. (April 2019) - Dowdy, Erin; DiStefano, Christine; Greer, Fred; Moore, Stephanie; Pompey, Kelvin
Screening for emotional and behavioral risk at the preschool level provides an opportunity to inform early intervention and prevention efforts. This study reports initial validation information for the Behavioral Assessment System for Children–Third Edition, Behavioral and Emotional Screening System, Parent Form–Preschool (BASC-3 BESS Parent-P). Using an Integrative Data Analysis framework, the BASC-3 BESS Parent-P latent structure was investigated using the norming sample from the BASC-3 ( n = 459) as well as two randomly split samples from the BASC-2 norming sample (development sample n = 770; validation sample n = 799). Five models were tested using confirmatory factor analyses; findings suggested a four-factor oblique solution, including Internalizing Risk, Externalizing Risk, Adaptive Skills, and Attention Problems factors. Future research directions and use in school-based screening applications are presented.